THE EFFECT OF AUGMENTED REALITY ON LEARNING OUTCOMES THROUGH ASSEMBLER EDUCATION APPLICATIONS IN ELEMENTARY SCHOOLS - Mutiara; Hermansyah; Yayuk Kusumawati (El Midad, 2025)
The Society 4.0 era is characterized by integrating technology into various sectors, including education, to improve learning effectiveness. One technology that has great potential in supporting the learning process is Augmented Reality (AR), which allows interactive and concrete visualization of abstract concepts. This study examines the effectiveness of using AR-based learning media through the Assembler Edu application in improving student learning outcomes in IPSA (Natural and Social Sciences) subjects at the elementary school level. The research approach used is quantitative with a pre-experimental one-group pretest-posttest Design to measure the effect of AR media on student understanding. The subjects of this study were 30 grade V students at MIN Kota Bima. Data collection techniques were conducted through tests, observations, interviews, and documentation. The results showed a significant increase in student learning outcomes, with an average pretest score of 54.16 and a posttest score of 85.5. The N-Gain value reached 0.78 or 78.01%, which is included in the high category. This finding shows that using the Assembler Edu application can improve students' understanding of abstract concepts in IPAS, encourage learning motivation, and create a more interesting and interactive learning experience. This research is expected to contribute to learning innovation at the elementary school level and become a reference for educators in choosing the right digital learning media.